Anti-CTLA-4 treatment induces IL-10-producing ICOS+ regulatory T cells displaying IDO-dependent anti-inflammatory properties in a mouse model of colitis. Issue 10 (7th June 2009) - Coquerelle, C; Oldenhove, G; Acolty, V; Denoeud, J; Vansanten, G; Verdebout, J-M; Mellor, A; Bluestone, J A; Moser, M
Abstract : Background and aims: Cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) has been shown to act as a negative regulator of T cell function and has been implicated in the regulation of T helper 1 (Th1)/Th2 development and the function of regulatory T cells. Tests were carried out to determine whether anti-CTLA-4 treatment would alter the polarisation of naive T cells in vivo. Methods: Mice were treated with anti-CTLA-4 monoclonal antibody (mAb) (UC10-4F10) at the time of immunisation or colonic instillation of trinitrobenzene sulfonic acid (TNBS). The cytokines produced by lymph node cells after in vitro antigenic stimulation and the role of indoleamine 2, 3 dioxygenase (IDO) and of interleukin-10 (IL-10) were tested, and the survival of mice was monitored. Results: Injection of anti-CTLA-4 mAb in mice during priming induced the development of adaptive CD4 + regulatory T cells which expressed high levels of ICOS (inducible co-stimulator), secreted IL-4 and IL-10. This treatment inhibited Th1 memory responses in vivo and repressed experimental intestinal inflammation. The anti-CTLA-4-induced amelioration of disease correlated with IDO expression and infiltration of ICOS high Foxp3 + T cells in the intestine, suggesting that anti-CTLA-4 acted indirectly through the development of regulatory T cells producing IL-10 and inducing IDO. Conclusions: These observations emphasise the synergy between IL-10 and IDO as anti-inflammatory agents and highlight anti-CTLA-4 treatment as a potential novel immunotherapeutic approach for inducing adaptive regulatory T cells.